Business Relationships between Corporations and Distributors: A Study of Petroleum Business Law in Indonesia - Santoso, Budi (International Journal of Criminology and Sociology, 2021)
The paper aims to analyze the business relationship in LPG (Liquefied Petroleum Gas) distribution and marketing in Indonesia as it has an important and strategic role for most Indonesian people. By using a juridical and empirical approach, the results showed that Pertamina is a state-owned company that assigns LPG duties to the end-user. To reaches the end-user needed by another intermediary, namely an agent. The legal relationship between Pertamina and the agent is stipulated in the agency contract. Form the theory side, it is necessary to research whether the agency contract is based on the basic principles of agency law or not. The incompatibility of an agency contract with the basic principles of agency law caused the contract not to have legal force. The contribution of this research is its examination of the legal validity of the agency contract of Pertamina with the agent and to provide a legal opinion from the agency theory side which should be the basis for making agency contracts.